Comparison of Three Types of Continent Urinary Diversions in a Single Center. (2004) - Girgin, Cengiz; Sezer, Akif; Ozer, Kutan; Tarhan, Huseyin; Bolukbasi, Ahmet; Gurel, Gozen
Abstract : The results including the complication and continence rates for 3 types of continent urinary diversion were evaluated. From 1992 to 1998 we performed 58 continent urinary diversions after radical cystectomy for invasive transitional cell carcinoma (TCC) of the urinary bladder. All three types of continent diversions and ileal loop procedures were discussed and patient preferences were determined. The patient preference rate for continent urinary diversion was 96.6%, and half of these patients wanted to be completely dry. Mean age of the patients was 58.2 years. Of the 58 patients, 9 (15.5%) had a Kock pouch, 15 (25.8%) had a Kock neobladder and 34 (58.6%) had sigmoidorectal pouch (Mainz-II pouch). Early and late complication rates of the three different continent diversions were evaluated. The number of complications, such as urine leakage, pyelonephritis, hydronephrosis, reflux and stone formation, were similar in all three types of diversions. Two (5.9%) Mainz pouch II patients who had stopped oral alkalinization demonstrated severe hyperchloremic acidosis. Spontaneous pouch rupture occurred in 1 of the Kock pouches. Reoperation rates were higher with the Kock pouch and Kock neobladder cases. Daytime continence rates for the Kock pouch, Kock neobladder and Mainz II pouch were 77.7%, 86.7% and 100% respectively. Even though complete dryness may not be achieved in every patient, orthotopic bladder substitution appears to be the best choice after radical cystectomy. Although it carries the risk of life-long oral alkalinization therapy, the Mainz pouch II is associated with an excellent continence rate and may be a good alternative for patients who desire to be dry.